1987
DOI: 10.1002/jbmr.5650020509
|View full text |Cite
|
Sign up to set email alerts
|

A simple spectrophotometric assay for micromolar amounts of lanthanum in the presence of calcium and phosphate

Abstract: A sensitive spectrophotometric assay for micromolar amounts of lanthanum in the presence of calcium and phosphate (as hydroxyapatite) was developed utilizing the change in absorption (at 652 nm) when the dye arsenazo III was complexed with lanthanum. Arsenazo III was used at a level of 25 microM and the solution pH was maintained at 3.1 with 0.2 M sodium acetate. Lanthanum concentrations down to 0.5 microM could be reliably assayed. Calcium ion did not complex well with arsenazo III at pH 3.1. With calcium pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…For concentrations higher than 2 μM, an additional peak can be detected at 600 nm under certain conditions. This observation has also been made by Fernandez-Gavarron et al, who detected an additional peak at 597 nm when using a mixture of 25 μM AS III and 10 μM La at pH 3.1 ( 30 ). Since the pH of the cultivation medium varies during microbial growth, pH must be monitored and adjusted for the assay.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…For concentrations higher than 2 μM, an additional peak can be detected at 600 nm under certain conditions. This observation has also been made by Fernandez-Gavarron et al, who detected an additional peak at 597 nm when using a mixture of 25 μM AS III and 10 μM La at pH 3.1 ( 30 ). Since the pH of the cultivation medium varies during microbial growth, pH must be monitored and adjusted for the assay.…”
Section: Resultssupporting
confidence: 79%
“…1 ). REEs readily hydrolyze at an acidic pH and can thus be analyzed in the presence of calcium and other metal cations ( 30 ). While no crystal structure of an AS III complex with metal ions is available, it has been proposed that AS III forms 1:1 complexes with metals and that only one arseno group is involved in metal binding ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, La and other rare earths are known as Ca-substituting ions in apatites [10]. Another paper has reported that exchange of La for calcium in the apatite matrix may be responsible for increased resistance of hard tissues to acid dissolution [11]. However, the effect of rare earth elements, such as La, in HA biological performance will be clarified if cell culture studies will be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, given the aforementioned similarity in biophysical and biochemical characteristics between Ca(II) and La(III), uptake and retention in bone tissue was observed, with evidence that lanthanum readily exchanged with calcium in the HAP-like mineral matrix. 30 What was surprising though was the effect that lanthanum had on the bone remodelling cycle, with various studies suggesting that at certain lanthanum concentrations, the proliferation of bone-building osteoblasts was promoted, leading to an increase in the rate of mineralization and bone formation. 31 Since osteoporosis is a condition in which the rate of bone resorption outweighs that of bone formation, it was hypothesized that a compound containing lanthanum could be used in the treatment and/or therapy for such diseases.…”
Section: Lanthanum Carbonatementioning
confidence: 99%